Ewing’s sarcoma of the mediastinal extraosseous site: a case report of a rare occurrence with literature review - Zhou, Hong; Su, Meng; Wang, Han-Fang; Feng, Si-Qi; Jiang, Wen-Qian; Li, Xiao-Rong (Frontiers in Oncology, 2025)
ObjectiveTo present a rare case of mediastinal extraosseous Ewing sarcoma(EES), broadening the body of knowledge already in existence on EES. This paper intends to give doctors more diagnostic and therapeutic understandingMethodsThe patient’s imaging data was analyzed retrospectively. We identified and compiled the distinctive imaging characteristics of mediastinal EES by combining these results with histopathological evaluation and a review of relevant literature.Key findingsTypical imaging features of mediastinal EES include a large, bulky mass with irregular shape and lobulated, poorly defined margins. On computed tomography (CT), it often shows heterogeneous density along with infiltration of nearby organs and anatomical structures.ConclusionMediastinal EES is a rare and clinically challenging diagnosis. However, recognition of its characteristic imaging features may facilitate radiological diagnosis. Nevertheless, histopathological confirmation remains the gold standard for definitive diagnosis.